MegaLMM: Mega-scale linear mixed models for genomic predictions with thousands of traits. - Runcie, Daniel E.; Qu, Jiayi; Cheng, Hao; Crawford, Lorin (Genome Biology, 2021)
Large-scale phenotype data can enhance the power of genomic prediction in plant and animal breeding, as well as human genetics. However, the statistical foundation of multi-trait genomic prediction is based on the multivariate linear mixed effect model, a tool notorious for its fragility when applied to more than a handful of traits. We present MegaLMM, a statistical framework and associated software package for mixed model analyses of a virtually unlimited number of traits. Using three examples with real plant data, we show that MegaLMM can leverage thousands of traits at once to significantly improve genetic value prediction accuracy.